Nonmedical use of prescription opioids and pain in veterans with and without HIV. - Barry, Declan T; Goulet, Joseph L; Kerns, Robert K; Becker, William C; Gordon, Adam J; Justice, Amy C; Fiellin, David A (Pain, 2011)
Few studies have systematically evaluated nonmedical use of prescription opioids (NMU) among U.S. military veterans, those who report pain, and those with human immunodeficiency virus (HIV). An increased understanding of the factors associated with NMU may help providers to balance maintaining patient access to prescription opioids for legitimate medical reasons and reducing the risks of addiction. We analyzed self-report data and electronic medical and pharmacy record data from 4122 participants in the Veterans Aging Cohort Study. Bivariate associations were analyzed using chi-squared tests, t tests, and median tests, and multivariable associations were assessed using logistic regression. Median participant age was 52 years; 95% were men; 65% were black, and 53% were HIV infected. NMU was reported by 13% of participants. In multivariable analysis, NMU was associated with: being Hispanic (adjusted odds ratio [AOR] 1.8); aged 40-44 years (AOR 1.6); Alcohol Use Disorders Identification Test score ≥20 (AOR 2.0); drug use disorder (AOR 1.9); opioid use disorder (AOR 2.7); past month cigarette use (AOR 1.3); receiving a past-year Veterans Health Administration opioid prescription (AOR 1.9); hepatitis C (AOR 1.5); and pain interference (AOR 1.1). Being overweight (AOR 0.6) or obese (AOR 0.5) and having a higher 12-Item Short-Form Health Survey (SF-12) Mental Component Summary (AOR 0.98) were associated with less NMU. Patients with and without NMU did not differ on HIV status or SF-12 Physical Component Summary. Veterans in care have a high prevalence of NMU that is associated with substance use, medical status, and pain interference, but not HIV status.
Keywords: Adult; Aged; Analgesics, Opioid; Chi-Square Distribution; Cohort Studies; Female; Health Surveys; HIV Infections; Humans; Logistic Models; Male; Mental Disorders; Middle Aged; Odds Ratio; Opioid-Related Disorders; Pain; Pain Measurement; Prescriptions; Psychiatric Status Rating Scales; Questionnaires; Retrospective Studies; Self Report; Veterans Health; Young Adult